2021
DOI: 10.36547/ams.27.2.952
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Mechanical and Tribological Behaviour of Aisi 316l Stainless Steel During Salt Bath Nitriding

Abstract: The aim of the current work was to analyse the impact of salt bath nitriding on the behavior of the tribological characteristics and surface microstructures of AISI 316L stainless steels. Nitriding was carried out at 580°C for 10 h. The tribological, structural behavior of the AISI 316L before and after salt bath nitriding was compared. The surface microstructures, tribological characteristics, as well as its surface hardness, were investigated using optical microscopy (OM), X-ray diffractometer (XRD), surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Very recently, the tribological properties of steel have been improved by the salt-nitrating treatment process. It was reported that optimum wear resistance and the frictional coefficient can be obtained by increasing the temperature of the salt solution [11]. The stainless steel grade-316 medical plates are surface coated using the QPQ method to improve hardness and reduce wear loss using the Taguchi method [12].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the tribological properties of steel have been improved by the salt-nitrating treatment process. It was reported that optimum wear resistance and the frictional coefficient can be obtained by increasing the temperature of the salt solution [11]. The stainless steel grade-316 medical plates are surface coated using the QPQ method to improve hardness and reduce wear loss using the Taguchi method [12].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the tribological properties of the steel is improved by the salt nitrating bath treatment process. It was reported that wear resistance and frictional coefficient have been reached to maximum level by increasing the temperature of the salt solution [11]. As per the above-mentioned literature, the process parameters of the QPQ method have not been performed to optimize the hardness and layer thickness.…”
Section: Introductionmentioning
confidence: 99%